Kajian Awal terhadap Potensi Kawasan Konservasi Taman Buru Gunung Masigit Kareumbi, Jawa Barat dalam Upaya Pengembangan Ekowisata - Deni Deni (Jurnal Ilmu Kehutanan, 2010)
Preliminary Study of Potentiality of Hunting Park of Mt. Masigit KareumbiConservation Area, West Java for Ecotourism DevelopmentMasigit Kareumbi Hunting Park, with all its uniqueness, specificity, beauty, natural phenomena, landscape and ecosystem types is the basis of capital whose existence required to be continuously explored and analyzed in order to develop ecotourism development. Ecotourism potential of Masigit Kareumbi Hunting Park have not been optimally managed to develop as ecotourism product to improve the life quality of surrounding local communities. This research was conducted to provide information on potential development of Masigit Kareumbi Hunting Park. Field survey was performed to determine the selected locations that can strategically be developed as natural tourism objects. The results of the study showed that Masigit Kareumbi Hunting Park had the diversity potencies of flora, fauna, landscape and ecosystem types potential to be developed for ecotourism products. These potencies should be optimized for the hunting park as well as to increase income of local community.